4(6+7)=4*6+x*7

Simple and best practice solution for 4(6+7)=4*6+x*7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6+7)=4*6+x*7 equation:


Simplifying
4(6 + 7) = 4 * 6 + x * 7

Combine like terms: 6 + 7 = 13
4(13) = 4 * 6 + x * 7

Multiply 4 * 13
52 = 4 * 6 + x * 7

Multiply 4 * 6
52 = 24 + x * 7

Reorder the terms for easier multiplication:
52 = 24 + 7x

Solving
52 = 24 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
52 + -7x = 24 + 7x + -7x

Combine like terms: 7x + -7x = 0
52 + -7x = 24 + 0
52 + -7x = 24

Add '-52' to each side of the equation.
52 + -52 + -7x = 24 + -52

Combine like terms: 52 + -52 = 0
0 + -7x = 24 + -52
-7x = 24 + -52

Combine like terms: 24 + -52 = -28
-7x = -28

Divide each side by '-7'.
x = 4

Simplifying
x = 4

See similar equations:

| s=-16t^2+128t+144 | | 18xy-3x-19xy= | | 24x^2+91x+72=0 | | 5G/7=18 | | -14.1+18.3= | | 4x+9=12+3x | | -7/2-2x=-1/2 | | ((4x^2)-2x+6)/(2x-3) | | 65-7x=2x+23 | | -5(k+3)+4k=3(k-5) | | 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= |

Equations solver categories